Peran Suami Dalam Mewujudkan Keharmonisan Rumah Tangga (Studi Pemikiran Ash-Shan’ani Dalam Kitab Subulussalam) - Arum Tazkya Maharani, Rifa; Zaki, Muhammad; Fariz Amrullah D, M Dani (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to analyze Muhammad bin Ismail Ash-Shan‘ani’s perspective in Subulussalam regarding the husband’s role in achieving household harmony. Using a qualitative method with a textual and content analysis approach, this research explores Ash-Shan‘ani’s interpretation of a husband’s rights and obligations in fostering a harmonious, loving, and merciful family. The findings reveal that Ash-Shan‘ani emphasizes the husband’s leadership role as a provider, protector, and spiritual guide who must uphold moral integrity in interactions with his wife. Harmony in the household, according to Ash-Shan‘ani, can be realized through mutual fulfillment of rights and duties, effective communication, and adherence to Islamic ethical principles. His thought offers a comprehensive framework that integrates emotional, material, and spiritual responsibilities within marriage. Furthermore, this classical perspective remains relevant in addressing contemporary family challenges by promoting justice, compassion, and mutual respect as the foundation of marital harmony in Islamic teachings.